Admiralty Method of Tidal Prediction (Form NP 159) Refinements and Increase in Accuracy - Merriman, A. G. (The International Hydrographic Review, 2015)
This paper is intended to supplement the paper ‘Admiralty method of tidal prediction, NP 159’ by Commander N.C. G len , R.N., published in the International Hydrographic Review, LIV(l), January 1977 [1], and should be read in conjunction with that paper. The Admiralty Form NP 159 [2] is a simplified graphical method of obtaining a predicted tidal curve which gives a good approximation to that produced by a full prediction using far more data. Although at first sight it may appear rather tedious, no other method of comparable accuracy approaches its simplic ity; thus, although any gain in accuracy is welcomed, any such gain must be weighed against simplicity of application if it is not to destroy the essential character of the method. This criterion has been carefully taken into account when designing these improvements. The first part of the paper concerns the simple application of an additional 5 constituents, while the second part shows how a programmable calculator can increase not only the ease of operation but also the accuracy of prediction by removing some approximations which have to be made in order to keep the drawing task within reasonable proportions.